Culture as an attribute of digital transformation - S. V. Firsova; O. M. Danilina; A. A. Dashkov; V. Yu. Pokazanyev (Цифровая социология, 2021)
The article comprehends the concept of digital culture that appeared with the beginning of the information/digital era at the end of the last century. The paper considers digital culture from the point of view of the general resource of the knowledge society and as a new social ecology that determines the experience and capabilities of people at the present time, when the digital network environment has brought new practices, opportunities and threats. Speaking about culture in the context of information and communication technologies, the authors emphasize that its influence is even more significant, since the way it is used can affect the change in the essence of our communication and cultural models and become a support for the digital transformation of organizations. Digital culture is understood as the way that society uses to receive and process information. It is required to comprehend and create a new digital culture as a guarantor of the implementation and adoption of changes in the context of widespread digitalization and rethinking of business processes, distribution channels and relations with consumers, leading, in turn, to a change in the value proposition and the consumer segments themselves. Based on the analysis, the authors formulate and substantiate five main reasons why building a digital culture should become a key problem for the successful development of any organization: 1) digital transformation will not be complete without the development of a thriving digital culture; 2) insufficient organizational culture is detrimental to success in the digital age; 3) a strong digital culture is a competitive advantage for an organization; 4) a strong digital culture is the key to business longevity; 5) using a digital culture can increase employee engagement in the work process.